A critical analysis on the energy and exergy performance of photovoltaic/thermal (PV/T) system: The role of nanofluids stability and synthesizing method. (June 2022) - Masoud Parsa, Seyed; Yazdani, Alireza; Aberoumand, Hossein; Farhadi, Yousef; Ansari, Abolfazl; Aberoumand, Sadegh; Karimi, Nader; Afrand, Masoud; Cheraghian, Goshtasp; Muhammad Ali, Hafiz
Graphical abstract: Highlights: The effect of nanofluid stability and synthesizing methods on the performance of PV/T was evaluated. The effect of flow regime in different types of nanofluids on PV/T system was assessed. Energy and exergy analysis by considering each preparation method was conducted. The maximum efficiencies were obtained from turbulent flow regime and one-step method prepared nanofluid. EEW method as the one-step procedure in this study showed excellent stability for a longer time than that using ultrasonication process. Abstract: The main aim of this paper is to realize for the first time the effect of nanofluid preparation method on the performance of photovoltaic/thermal (PV/T) system in a comparative experimental study. Silver nanofluid via one-step and two-step method at different concentrations of 1%, 3%, and 5% were prepared. The stability of nanofluid at all concentrations was measured via zeta-sizer before and after experiments and the results showed the stability of nanofluid in one-step prepared is significantly higher than two-step. It was elucidated that the energy and exergy of the PV/T for one-step nanofluid substantially improved compare to the two-step preparation method. Moreover, it was found that by increasing nanofluid from 1 to 3% and 3 to 5% in one-step method all efficiencies were linearly increased but for two-step prepared nanofluid the maximum rate of enhancement was obtained from 1 to 3%. It was observed that when system operated with two-step prepared nanofluid, performance of the system for 3% at turbulent-flow regime is higher than 5% at laminar-flow regime which directly related to the stability of nanofluid. Based on our results it can be concluded that nanofluid preparation method and its stability also play crucial roles on the performance of PVTs.